Quantitative Analysis of Surgical Working Space During Endoscopic Skull Base Surgery - Davies, Joel C.; Chan, Harley H.L.; Yao, Christopher M.K.L.; Cusimano, Michael D.; Irish, Jonathan C; Lee, John M (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives Selective dissection of intranasal anatomy may improve visualization and maneuverability at the skull base. We aimed to quantify the dimensions of working space and angles achieved following sequential removal of intranasal structures using an endoscopic transphenoidal approach to the skull base.Methods Cone beam computed tomography scans of four cadaveric heads were obtained for registration of an optical tracking system. Each head was sequentially dissected: (1) sphenoidotomy and limited posterior septectomy, (2) unilateral partial middle turbinectomy, (3) bilateral partial middle turbinectomy, and (4) wide posterior septectomy. The maximal craniocaudal and mediolateral distance (mm) and angle (degrees) reached were calculated at the sphenoid face and sella. Data were analyzed using descriptive statistics and tests of statistical significance. The significance level was set at p  ≤  0.05.Results A significant improvement in both dimensions of working space was observed with each stage of dissection at the level of the sphenoid face. Maximal working space was achieved following bilateral middle turbinectomy and wide posterior septectomy with a 38 and 29% increase in working space in the mediolateral and craniocaudal dimensions, respectively. The largest stepwise increase in working space was observed with unilateral middle turbinectomy (mediolateral: 24 ± 3 mm and craniocaudal: 20 ± 3 mm). A trend toward improved degrees of visualization was observed with each stage of dissection but was not statistically significant.Conclusion Approaches to the skull base can be enhanced by selective unilateral/bilateral partial middle turbinectomy and posterior septectomy being performed to improve visualization and maximize surgical working freedom.
Keywords: endoscopic surgery; skull base anatomy; transsphenoidal; three dimensional modeling